2018
DOI: 10.1111/asj.13066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an immunomodulatory feed additive on body weight, production parameters, blood metabolites, and health in multiparous transition Holstein cows

Abstract: The study investigated the impact of feeding OmniGen-AF â (OG; Phibro Animal Health, Quincy, IL) from dry-off to week 4 of lactation at two doses on production performance and metabolic adaptation of multiparous Holstein cows. Forty-eight cows were blocked and assigned randomly to three treatments: OG was fed at 0 g/ head/day (CON), 60 g/head/day (OG60), or 90 g/head/day (OG90). No difference was observed in dry matter intake (DMI) throughout the experiment, whereas feeding OG tended to decrease the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
4
1
Order By: Relevance
“…However, this reduction was more evident in OMN fed cows during the second half of the challenge, becoming significantly greater than in CON cows at d 21 and 28 ( Figure 5 c). This suggests a better energy balance of OMN fed cows, as previously suggested by Wu et al [ 15 , 78 ] and could be explained by the energetic cost of inflammation. Inflammation changes the prioritization of nutrients, affecting energy balance and performance [ 22 ].…”
Section: Discussionsupporting
confidence: 79%
“…However, this reduction was more evident in OMN fed cows during the second half of the challenge, becoming significantly greater than in CON cows at d 21 and 28 ( Figure 5 c). This suggests a better energy balance of OMN fed cows, as previously suggested by Wu et al [ 15 , 78 ] and could be explained by the energetic cost of inflammation. Inflammation changes the prioritization of nutrients, affecting energy balance and performance [ 22 ].…”
Section: Discussionsupporting
confidence: 79%
“…We did not observe greater clinical signs in the cows included in this analysis, which may have contributed to the observed metabolic changes. The serum concentrations recorded in this study were lower compared to a previous study conducted in the same facility [25] as well as experiments with similar low protein diets prepartum [26,27]. Under non-inflammatory conditions Ca is under hormonal control [24].…”
Section: Blood Parameters In Cows and Calvescontrasting
confidence: 79%
“…Previous research reported that most respiratory diseases in the feedlot occurred within the first 30 days after arrival (27). Therefore, the greater growth performance observed in calves supplemented with NTG during the first weeks of the experiment may be associated with a greater immune response to challenges being faced during the receiving period, as has been suggested in previous studies (1)(2)(3)(4)6). However, in agreement with the current study, Colombo et al (6) did not observe an overall effect on growth performance when crossbred yearling cattle were fed a similar immunomodulatory supplement in the feedlot.…”
Section: Discussionmentioning
confidence: 65%
“…NutraGen (NTG; Phibro Animal Health, Teaneck, NJ, USA) contains similar properties to OmniGen (OMG; Phibro Animal Health, Teaneck, NJ, USA), which is used in the dairy industry (2). Previous research has reported that the use of this blend in dairy cows' diets includes improved metabolic response to a glucose tolerance test (2), modulation of inflammatory responses (3), increased milk production (4), and enhanced immunomodulatory response to heat stress (5,6). The latter may be particularly relevant for enhancing growth performance responses in feedlot cattle during extreme ambient temperatures.…”
mentioning
confidence: 99%